2018
DOI: 10.1007/s00520-018-4165-6
|View full text |Cite
|
Sign up to set email alerts
|

Addition of doxycycline to ciprofloxacin for infection prophylaxis during autologous stem cell transplants for multiple myeloma

Abstract: The addition of doxycycline to standard prophylaxis with ciprofloxacin seems to reduce the number of NF episodes and documented bacterial infections in patients with MM undergoing ASCT, without increasing rate of serious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…Certain antibiotics (e.g., doxycycline, fluoroquinolones, rifabutin, nitroxoline, etc.) have been shown to exhibit anti-cancer activity and have been studied in clinical trials [ 29 - 32 ]. Like many forms of cancer, including colorectal cancer (CRC), angiogenesis is an important pathway in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Certain antibiotics (e.g., doxycycline, fluoroquinolones, rifabutin, nitroxoline, etc.) have been shown to exhibit anti-cancer activity and have been studied in clinical trials [ 29 - 32 ]. Like many forms of cancer, including colorectal cancer (CRC), angiogenesis is an important pathway in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to identify novel repurposable drugs that could increase the cytotoxicity of antimitotic drugs to P-gp-overexpressing drug-resistant cancer cells. Various antibiotic drugs can be used in cancer therapy [14,15,17]. Thus, we attempted to identify novel repositioned drugs from antibiotics and determine whether the co-treatment of various antibiotics could increase the cytotoxicity of antimitotic drugs in drug-resistant KBV20C cancer cells.…”
Section: Vic + Rifabutin Exhibits Increased Cytotoxicity In P-gp-over...mentioning
confidence: 99%
“…Antibiotics (doxycycline, levofloxacin, fluoroquinolones, nitroxoline, rifabutin, etc.) exhibit anticancer activity and have been used in clinical trials as repositioned drugs for cancer patients [14][15][16][17]. Further, we evaluated antibiotics with potential cytotoxic effects when administered as a co-treatment with antimitotic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, a randomized phase III study that included 212 MM patients undergoing induction therapy showed that the prophylactic use of antibiotics did not decrease the incidence of serious bacterial infections, thus obviating the need for the routine use of antibacterial prophylaxis in Update on Multiple Myeloma patients with MM receiving induction therapy [76]. However, other studies have shown that the addition of doxycycline to ciprofloxacin and the sequential use of levofloxacin followed by ertapenem in patients with MM subjected to autologous HSCT reduce the frequency of FN episodes, bacteremia, and documented bacterial infections without increasing the rate of serious complications [77,78].…”
Section: Bacterial and Bloodstream Infections In MMmentioning
confidence: 99%